Education for the Crossroads? A Short History of Social Work Education in Scotland. Issue 4 (8th August 2018) - McCulloch, Trish
Abstract : This paper provides a short history of social work education in Scotland. Its aim is to understand the patterns of the present through the lens of the past. A key argument is that social work education and practice exists persistently in the crossroads, that is, in the spaces between competing and often conflicting perspectives regarding that 'what', 'why', 'how' and 'who' of social work and social change. At the same time, there is a dearth of robust theory and research underpinning social work education and practice, leaving the profession vulnerable in periods of rapid social and political change. Attention is given to the implications of these constants for education and practice, and to how we might address these going forward. The paper concludes that if we wish to realise the potential of social work education, learning and practice, we need to more collectively address long-neglected questions of learning identity, learning philosophy and learning practice.